Chaihu Shugan powder restores fatty acid synthesis to alleviate insulin resistance in metabolic syndrome by regulating the LXRα/SREBP-1 signaling pathway - Lei, Sisi; Peng, Weihang; Wu, Lulu; Yu, Liyuan; Wang, Meida; Li, Qingmin; Deng, Yi; Zhao, Shuai; Huang, Peiying; Chen, Bojun (Frontiers in Pharmacology, 2024)
Background: Metabolic syndrome (MS) is a significant risk factor for cardiovascular and cerebrovascular diseases, primarily driven by insulin resistance (IR). Although the herbal compound Chaihu Shugan powder (CSP) has demonstrated the potential to improve IR in animal models of MS, its mechanism of action remains incompletely understood. Therefore, this study aimed to investigate the biological pathways through which CSP exerts its therapeutic effects on IR in MS using both in vitro and in vivo methods.The primary metabolites of CSP aqueous extract and CSP-containing serum were measured by LC-MS/MS. A mouse model of MS-related IR was induced by a high-fat, high-fructose diet combined with chronic immobilization stress. The CSP's therapeutic potential was evaluated through glucose and insulin tolerance tests and hepatic insulin signaling molecules (p-IRS-1, IRS-1, p-Akt, and Akt). The expression of lipid metabolism-related factors (FFA, DAG, LXRα, SREBP-1, FASN, and ACC) in the liver was also measured. Hepatocyte IR was modeled using high-glucose and high-insulin conditions, and CSP impact was evaluated using 2-NBDG uptake and insulin signaling molecule expression. The specific mechanism of CSP was explored using the LXRα agonist T0901317.The MS-related IR model exhibited a decreased p-Akt/Akt ratio and increased fasting glucose, insulin, homeostatic model assessment of IR, and hepatic lipid metabolism factors. Treatment with CSP mitigated these effects. In the hepatocyte IR model, CSP-containing serum improved glucose uptake and modulated the expression of insulin signaling and lipid metabolism factors. Furthermore, T0901317 reversed the beneficial effects of CSP, indicating the role of LXRα in CSP's therapeutic action.The CSP ameliorated IR in MS by restoring fatty acid metabolism through the regulation of the LXRα/SREBP-1 signaling pathway.